Nursing team perceptions about the use of a check list for counting surgical material - Cavalcante, Antonia Abigail do Nascimento (2022)
The objective was to analyze the perception of professionals in relation to the practice of counting surgical material and their needs in relation to the checklist for counting surgical material. For that, a qualitative study of the descriptive type was carried out, in the years 2018 and 2019, in three surgical centers in hospitals in a Brazilian municipality located in the interior of the state of Ceará. The participants were mid-level and higher-level nursing workers working in the surgical centers of these hospitals, totaling 138 employees. Questionnaires, forms and conversation circles were used for data collection. For the analysis, it was anchored in the categorical content analysis proposed by Bardin, which had the help of the Nvivo software. Thus, two categories emerged: Perceptions of nursing professionals about the surgical material counting checklist and Contributions to the improvement of the surgical material counting checklist. Initially, the implementation of the routine of checking and verifying the surgical material was considered by the professionals as something difficult and without the need to be used, however, after qualification and training, they started to consider it as a measure that provides support for their practice, however it is important that it occurs jointly with the other professionals involved in the surgical act. Furthermore, the instruments suited to the profile and the assistance characteristics of the institution stand out. Thus, practices for safe surgery involve all members of the surgical team, however, in most cases, this attribution is the responsibility of the nursing team.